O projeto de modernização de São Luís nos anos Paulo Ramos (1936-1945) - COSTA, Marcelo Lima (2016)
This study seeks to understand the urban reforms processed in the capital of Maranhão – São Luís, during the years Paulo Ramos (1936 to 1945) in the light of the sets of modernizing bias assumptions that campeavam the political debate in the country in those years as well as understand the limitations and the impacts such premises provided to ludovicenses, jealous of the trajectory of their city: one capital 'museum' on the way to modernize. From this we will discuss the national and state political relations that engendered the arrival of politicians promised as the modernization project (from the political issues, through the commercial and tax relations to the proposed interventions in urban space, especially). Therefore we will access the official speeches from the decrees, ordinances, laws and official speeches of managers (the governor / intervenor Paulo Ramos and mayors Saboya Ribeiro and Pedro Neiva) as well as the speeches of the newspaper O Imparcial, Acção, Diário do Norte and O Globo, in addition to the Diário Oficial, locus of debate on city issues, taking positions sometimes ambiguous in relation to the modernizing process of intervention of the municipal and state governments, sometimes praising the urban intervention process, sometimes criticizing him vehemently.